Pengaruh Operating Leverage, Financial Leverage, dan Combination Leverage Terhadap Earning Per Share Pada Perusahaan Jasa Sub Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia - Muhammad Faturinaldi; Edy Suryadi; Heni Safitri (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of variable Operating Leverage, Financial Leverage and partial leverage on Earning Per Share. The data used in the study is secondary data, obtained from the IDX, namely the financial statements from 2014-2016. The population used in this study amounted to 48 service companies in the property and real estate sub-sectors that are still listed on the Indonesia Stock Exchange in the 2014-2016 period. The sample selection technique uses purposive sampling method and obtained 41 service companies in the property and real estate sub-sectors used as samples. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis, partially Operating Leverage had no effect on Earning Per Share, Financial Leverage did not affect Earning Per Share, and Combination Leverage did not affect Earning Per Share. Simultaneous test results show that the regression model can be used to predict Earning Per Share as evidenced by a significant value of F of 0.988. R-Square value of 0.001 shows that the ability of independent variables in explaining the variation of the dependent variable is 0.1% and the remaining 99.9% is explained by other variables outside the research model.